Give the equation of the graph:
![\text{ f(x) = }\lvert x-2\rvert\text{ + 3}](https://img.qammunity.org/2023/formulas/mathematics/college/jsp4y46ksdovtsd9cb2hm492vgjp3ctsrq.png)
If it's been shifted by one unit to the left and two units downward, it means that the x-intercept will be subtracted by one unit and its y-intercept will be subtracted by two units.
Let,
g(x) = the new equation after being shifted
We get,
![\text{ f(x) = }\lvert x-2\rvert\text{ + 3 }\rightarrow g(x)\text{ = f(x-1) - 2}](https://img.qammunity.org/2023/formulas/mathematics/college/736ugez70aiceh9l5mt0j50n2cu7khpjlc.png)
![g(x)\text{ = }\lvert(x-1)-2\rvert\text{ + 3 - 2}](https://img.qammunity.org/2023/formulas/mathematics/college/607q202j0v4v4igsk5vqlzle9lft7etwxz.png)
![\text{ g(x) = }\lvert x-3\rvert\text{ + 1}](https://img.qammunity.org/2023/formulas/mathematics/college/gjrxf553q04c9tha2grmqruz7298ytc4dk.png)
Therefore, the new equation of the graph after being shifted will be g(x) = Ix-3I + 1.